Factor identification of website usability characteristics to end- user satisfaction: a case study at University of Colombo - Silva, M.A.L. (My University, 2015)
The case study aims to identify the pattern of correlation of the usability characteristics in the library website of the University of Colombo with respect to user satisfaction. A questionnaire based survey was carried out using 125 undergraduates in four faculties namely, Arts, Education, Law and Management & Finance. Factor analysis identified eleven dimensions that explain the pattern of correlation of the usability characteristicsin the library website in the study context for user satisfaction.In future the library professionals should consider these factors and the pattern of correlation of features when improving and redesigning the library website of the University of Colombo
Keywords: User Satisfaction, Library, Websites, Factors